2017
DOI: 10.1159/000484242
|View full text |Cite
|
Sign up to set email alerts
|

Use of Genetic Testing after Abnormal Screening Ultrasound: A Descriptive Cohort Study

Abstract: Background/Aims: The study aimed to characterize the use of genetic testing after abnormal screening ultrasound. Methods: We performed a retrospective review of patients undergoing genetic testing after abnormal ultrasound. Genetic evaluation consisted of noninvasive prenatal screening (NIPS) or amniocentesis. Classification of ultrasound findings, type of genetic testing, and results were collected. Results: A total of 139 subjects underwent genetic evaluation after abnormal screening ultrasound. Screening vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Abnormalities on ultrasound (US) are useful markers for detecting trisomy 21, trisomy 18, trisomy 13, sex chromosome aneuploidy (SCA), rare autosomal trisomies (RATs), and even copy number variations, as reported previously (Beulen, Faas, Feenstra, Vugt, & Bekker, 2017; DeVore, 2000; Shaffer et al, 2012). Clinically, the cardiac, neurologic, gastrointestinal, musculoskeletal, and facial defects are the most common ultrasonographic structural abnormalities as reported previously (Ainsworth, Holman, Codsi, & Wick, 2018; Rao & Platt, 2016), and nasal bone abnormalities, nuchal fold thickening, and hyperechoic bowel are useful at a fairly high detection rate for screening fetuses with trisomy 21 (Sonek & Croom, 2014). However, reports on the quantitative contribution of ultrasound toward identifying the genotypes of NIPS false‐negative cases are still limited.…”
Section: Introductionmentioning
confidence: 54%
“…Abnormalities on ultrasound (US) are useful markers for detecting trisomy 21, trisomy 18, trisomy 13, sex chromosome aneuploidy (SCA), rare autosomal trisomies (RATs), and even copy number variations, as reported previously (Beulen, Faas, Feenstra, Vugt, & Bekker, 2017; DeVore, 2000; Shaffer et al, 2012). Clinically, the cardiac, neurologic, gastrointestinal, musculoskeletal, and facial defects are the most common ultrasonographic structural abnormalities as reported previously (Ainsworth, Holman, Codsi, & Wick, 2018; Rao & Platt, 2016), and nasal bone abnormalities, nuchal fold thickening, and hyperechoic bowel are useful at a fairly high detection rate for screening fetuses with trisomy 21 (Sonek & Croom, 2014). However, reports on the quantitative contribution of ultrasound toward identifying the genotypes of NIPS false‐negative cases are still limited.…”
Section: Introductionmentioning
confidence: 54%
“…This suggested that CPM was sufficient to cause discordant NIPT results. Therefore, NIPT is still utilized as a screening test, and diagnostic confirmation must be performed on fetal cells from amniocentesis rather than chorionic villus sampling, in order to avoid CPM [34][35][36]. In this study, all diagnostic confirmation was derived from amniocentesis.…”
Section: Discussionmentioning
confidence: 99%
“…By accurately performing early pregnancy screening tests in the rst and second trimester, including double, triple, or quade tests and performing an ultrasound scan, the health status of the fetus can be determined to a large extent [13].…”
Section: Introductionmentioning
confidence: 99%